Exploration of Product Cost Literature In Indonesia: A Bibliometric Study and Systematic Review - Arif, Saiful; Tjatur, Christian; Handayati, Puji; Restuningdiah, Nurika (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to examine the trend of product cost research in Indonesia through a Systematic Literature Review (SLR) approach and bibliometric analysis. Data was obtained from the Scopus database with the keyword “product cost” in the Indonesian region in the range of 2015-2025, resulting in 174 documents. The analysis showed a significant increase in publications since 2020, with a peak in 2023. Institut Teknologi Sepuluh Nopember is the most productive and influential institution in the publication of this topic. The bibliometric visualization shows the existence of connected and unconnected authorship collaborations, as well as seven main keyword clusters that include supply chain, cost, and sustainability. Further analysis indicates that the integration of variable costing and absorption costing methods in the context of job order costing remains under-researched, despite its important implications in making more accurate cost decisions. This research provides a comprehensive overview of the development of product cost research in Indonesia and identifies research gaps that can be used as a basis for further studies.